The practicability of different preparation of mandibular molar restored by modified endocrown with intracanal extension: Computational analysis using finite element models. (November 2022) - Gong, Qimei; Huang, Luo; Luo, Junpan; Zhang, Yuejiao; Meng, Qingzhen; Quan, Jingjing; Tong, Zhongchun
Highlights: MED was considered a feasible way to restore defect molar under some conditions. Thicker MED by LU generated lower stress on tooth. MED by LU generated high stress around CEJ and low stress of tooth root. MED by EMAX formed low stress around CEJ and high stress in extended root canal. Abstract: Background and objective: Post-core-crown (PCC) and endocrown are two common restorative methods for severely damaged molars, but exhibit disadvantages. This study aimed to explore the practicability of modified endocrown with a 2 mm intracanal extension (MED) to restore defective teeth using finite element analysis (FEA). Methods: Five groups of numerical models of mandibular molars restored by three MEDs, a PCC, and a routine endocrown after root canal treatment were devised by FEA software. We constructed 4 mm, 3 mm, and 2 mm thickness of MED restorations to restore mandibular molars that were prepared to 1 mm, 2 mm, and 3 mm from the cemento-enamel junction (CEJ). Furthermore, PCC and routine endocrown were used to compare the stress distribution with MED. Lithium disilicate glass-ceramics (EMAX) and resin nanoceramics (LU) were considered restorative materials, and a vertical load of 600 N and an oblique load of 200 N were applied to the restorations. Results: In three MEDs by LU, 2 mm thickness of restoration generated the highest stress on prepared teeth, while the thickness of EMAX did not significantly influence the stress value. MED by LU generated higher stress around the CEJ, and reduced the stress on the middle and lower root compared to MEDs by EMAX, PCC by EMAX, and PCC by LU. MED by EMAX caused lower stress around the CEJ, and generated higher stress in the chamber walls after extended root canals compared with MED by LU, endocrowns by LU, and endocrowns by EMAX. There was an evident stress concentration at the last but one layer, which was a thin area of the tooth root in all restorative models. Conclusions: The use of modified endocrown may be considered an effective restorative method to restore defective mandibular molar, but suitable restorative material must be selected based on the tooth preparation method and deficiencies in the tooth structure. Graphical abstract: Image, graphical abstract